Evaluating the Effects of Motivational Interviews and Pharmacotherapies on Craving for Drugs Compared with Mere Pharmacotherapies - Anahita Mohammad Alizadeh Namini; Mohammad Esmaeilzadeh Akhoundi; Nahid Mohammad Safarlou (روانشناسی و روانپزشکی شناخت, 2017)
Introduction: Drug craving, generally thought as an uncontrolled desire for using narcotics, can bring about great psychological and physical sufferings such as anorexia, anxiety, insomnia, aggression and depression if not satisfied. Purpose: The purpose of the present study is to investigate the effects of medications and motivational interviews on treating addicts’ craving for drugs. The study endeavors to understand the effectiveness of motivational interviews along with pharmacotherapies on drug craving compared with treatments making use of just pharmacotherapy. Methodology: The study population included the Iranian addicts who have taken initiatives to quit their addiction. Available sampling was employed to select 20 individuals who were admitted to drug rehabilitation centers in Karaj. The two drug rehabilitation centers were Pars Arian and Ariana working under the supervision of the Ministry of Health and Treatment. Random sampling was employed to choose 10 addicts from each center among all the individuals who were admitted to the center during a time period of one month (10 addicts were place in the group of pharmacotherapy and 10 in the group of pharmacotherapy and motivational interview). Covariance and t-test were used to analyze the data. Results: According to the results, both methods affects the decrease of drug craving. Yet, the combination of motivational interviews with pharmacotherapy proved to be more effective than mere medication. Conclusion: Motivational interviews as a psychological intervention along with medication can play a significant role in decreasing drug craving.